STUDENTS’ PERFORMANCE IN RUSSIAN AND UZBEK-LANGUAGE INSTRUCTION CLASSES - Akhmadjonov , Khasan Akhmadjanovich (Educational Research in Universal Sciences, 2023)
Students in Russian-language instruction classes perform better than students in Uzbek-language instruction classes. The answer to the question “why is that” many people would like to know. Obviously, every year the number of parents who want their children to go to the former is on the increase because the graduates of the former are totally different in many aspects from the latter. In this article, I will make an effort to describe the differences in two types of language instruction classes and give reasons for students performing better in Russian-only instruction classes.